Inhibition Ras/MEK/ERK pathway: An important mechanism of Baihu Jia Guizhi Decoction ameliorated rheumatoid arthritis. (25th March 2023) - Chen, Qi; Yang, Jinming; Chen, Huan; Pan, Ting; Liu, Panwang; Xu, Shi-jun
Abstract: Ethnopharmacological relevance: Alleviating rheumatism by inhibiting synovitis is a routine treatment for rheumatoid arthritis (RA). Baihu Jia Guizhi Decoction (BHJGZ) is a classic prescription and has a long history of application for treating RA with a good anti-inflammatory action. However, the underlying molecular mechanisms have not been fully elucidated. Aim of the study: This work aimed to decipher the potential mechanism of BHJGZ against RA focusing on Ras/MEK/ERK pathway. Materials and methods: Based on the prediction of network pharmacology, the inhibition action of BHJGZ on Ras/MEK/ERK pathway was firstly validated in vivo and in vitro. Moreover, the affinity with the ingredients of BHJGZ in serum and the targets of Ras/MEK/ERK pathway were evaluated. Finally, the efficacy of BHJGZ for relieving RA was assessed in AA rats. Results: The Ras/MEK/ERK pathway was predicted by network pharmacology as one of important mechanisms of BHJGZ to treat RA. The high expression of Ras protein in synovitis of AA rats was significantly reduced by the treatment with BHJGZ, and the activation of Ras/MEK/ERK pathway in vivo and in vitro was also markedly inhibited ( p < 0.05 or p < 0.01). Moreover, the level of p-ERK/ERK, IL-6 and TNF-α in vitro were further suppressed after Ras or MEK was inhibited by mirdametinib or lonafarnib respectively ( p < 0.01). Furthermore, the results of molecular docking showed a good affinity and stable binding with the ingredients of BHJGZ in serum and multiple key proteins of the Ras/MEK/ERK pathway. Finally, paw swelling, paw circumference and pathological changes of joint synovitis were significantly reduced by BHJGZ in AA rats ( p < 0.05). Conclusion: The inhibition of Ras/MEK/ERK pathway is one of crucial mechanisms of BHJGZ for ameliorating synovitis of RA. Graphical abstract: Image 1 Highlights: The therapeutic effect of BHJGZ on rheumatoid arthritis was proved. It was demonstrated that BHJGZ can alleviate synovitis of rheumatoid arthritis. It was proved that BHJGZ could inhibit Ras/MEK/ERK signal pathway. This study provided a new idea for the treatment of rheumatoid arthritis.